THE EMPATHY DEFICIT: INVESTIGATING THE IMPACT OF MANAGERIAL EMOTIONAL COMPETENCE ON REMOTE TEAM PERFORMANCE AND ATTRITION - Nuraini; Ramon Zamora; Oktavianti (RADJA PUBLIKA, 2026)
The rapid shift toward remote and hybrid work has intensified the importance of managerial emotional competence in sustaining team effectiveness. This study investigates the concept of an “empathy deficit” in remote leadership and examines how managers’ emotional competence influences team performance and employee attrition. Drawing on a mixed-methods approach, the research combines survey data from remote employees with performance metrics and attrition records across distributed teams. The findings suggest that managers with higher levels of emotional competence—particularly in empathy, emotional regulation, and interpersonal awareness—foster stronger trust, communication quality, and psychological safety. These factors, in turn, are positively associated with higher team productivity and lower turnover intentions. Conversely, an empathy deficit in managerial behavior correlates with disengagement, miscommunication, and increased attrition rates. The study highlights the mediating role of perceived support and team cohesion in linking emotional competence to organizational outcomes. Implications are discussed for leadership development, remote management training, and organizational policy, emphasizing the need to prioritize emotional intelligence as a core managerial capability in distributed work environments.